Oral Health Knowledge Improvement Through Drama-Based Education in Elementary School Students - Jayanti, Revi; Fadjeri, Indrayati (Center of Excellent (Pusat Unggulan Iptek), 2026)
Background: Oral health is a critical aspect of children’s overall health, particularly during school age, with dental caries being a common problem. Knowledge of oral health is essential in shaping behaviors that promote proper dental hygiene. Objective: To assess the oral health knowledge of Grade V students at SDN Ratu Jaya 01 before and after an educational intervention using drama-based learning. Method: A pre-eksperimental study was conducted involving 60 students selected via total sampling. Data were collected using a structured questionnaire. Results: The findings revealed a significant improvement in students’ knowledge of oral health maintenance after the intervention. Prior to the drama-based educational session, many students demonstrated low levels of knowledge, whereas the majority exhibited good knowledge afterward. Conclusion: Drama-based learning is an effective medium to enhance oral health knowledge among elementary school students